Hierarchical porous nitrogen, oxygen, and phosphorus ternary doped hollow biomass carbon spheres for high‐speed and long‐life potassium storage. Issue 1 (9th December 2021) - Yang, Mengmeng; Kong, Qingquan; Feng, Wei; Yao, Weitang; Wang, Qingyuan
Abstract: Limited lithium resources have promoted the exploration of new battery technologies. Among them, potassium‐ion batteries are considered as promising alternatives. At present, commercial graphite and other carbon‐based materials have shown good prospects as anodes for potassium‐ion batteries. However, the volume expansion and structural collapse caused by periodic K + insertion/extraction have severely restricted further development and application of potassium‐ion batteries. A hollow biomass carbon ball (NOP‐PB) ternarily doped with N, O, and P was synthesized and used as the negative electrode of a potassium‐ion battery. X‐ray photoelectron spectroscopy, Fourier‐transform infrared spectroscopy, and transmission electron microscopy confirmed that the hollow biomass carbon spheres were successfully doped with N, O, and P. Further analysis proved that N, O, and P ternary doping expands the interlayer distance of the graphite surface and introduces more defect sites. DFT calculations simultaneously proved that the K adsorption energy of the doped structure is greatly improved. The solid hollow hierarchical porous structure buffers the volume expansion of the potassium insertion process, maintains the original structure after a long cycle and promotes the transfer of potassium ions and electrons. Therefore, the NOP‐PB negative electrode shows extremely enhanced electrochemical performance, including high specific capacity, excellent long‐term stability, and good rate stability. Abstract : The hierarchical porous N, O, and P ternary doped hollow biomass carbon spheres are used after hydrothermal–pyrolysis treatment in the potassium‐ion battery anode and show good long‐cycle stability and excellent rate performance.